Bullying In Michelle Julianto's The Nerd Can Fight: Pengintimidasian dalam Novel "The Nerd Can Fight" karya Michelle Julianto - Ana Khairiyah Utami Slamet; Adeline Grace Marianne Litaay (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This study discusses the kinds of bullying that Cassandra experiences, the causes, the effects and how Cassandra overcomes the bullying in Michelle Julianto's The Nerd Can Fight. The research applies descriptive qualitative method and psychological approach. After analyzing The Nerd Can Fight, the writer finds there are some forms of bullying experienced by Cassandra such as slapping, threatened by her friends, spreading rumor, and mocking. There are several underlying causes of the bullying on Cassandra, they include the fact that she is a nerd student, the death of Cassandra's brother, Maddison's taking revenge for Bryant's death, and lack of parental attention. Moreover, the effects of bullying on Cassandra are: having a kind of street fighting obsession, feeling hopeless, feeling upset, anxiety, and easily angry. There are several things that help Cassandra overcome the bullying effects: helping other people that can help Cassandra understand her pain, building self confidence and forgiving everyone who has hurt her. Keywords: bullying, kinds of bullying, causes of bullying, effects of bullying.